GOVERNMENT HEALTH EXPENDITURE AND INCLUSIVE GROWTH IN NIGERIA: THE ROLE OF INSTITUTIONS - ABANEME, ESTHER NGOZI; AJIBOLA, JOSEPH OLUSEGUN (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study empirically examined the effect of government health expenditure on inclusive growth and the role of institution in Nigeria from 1990-2023. The data were sourced from Central Bank of Nigeria Statistical bulletin (2023) and World Development Indicators database. Unit root test was conducted using Augmented Dickey Fuller (ADF) and Phillip Perron Statistics. Result from these tests indicated that the variables were integrated in order I (0) and I (1). Autoregressive Distributive Lag Model (ARDL) was employed. The result indicated that government health expenditure had positive significant effect on inclusive growth in the long run. The interaction of government health expenditure and institutional quality had positive insignificant effect on inclusive growth both in the short and long run. The study therefore concluded that institutions in Nigeria limit government effort in achieving inclusive growth. Based on the findings, we recommend that there should be total reform of Nigerian institutions by the government.